What is the Effect of Hyperbaric Oxygen Therapy on Pocket Depths as an Adjunct to Conventional Scaling and Root Planning? - Anna Winsness; Gabby Fallin; Krystal Herring, RDH, MPH (Elsevier, 2024)
OBJECTIVES: Hyperbaric oxygen therapy (HBOT) brings several benefits to wound healing in various tissues throughout the body by delivering high concentrations of oxygen under increased atmospheric pressure for small intervals of time. In addition to routine scaling and root planning (SRP), HBOT may be able to further improve pocket depths, revive tissues, and maybe even help to regenerate parts of the periodontal ligament. METHODS: The Augusta University Greenblatt online library, Google scholar, and Galileo were used to find credible articles. Criteria for finding credible articles included articles that were published within 5 years of 2023, articles that are not literature reviews, articles that report randomized clinical trials, and articles that do not present an obvious bias. RESULTS: All studies yielded results in favor of the use of HBOT to improve periodontal health. Results included decreases in probing depths, improved clinical attachment levels, decreases in bleeding, and improved gingival indexes. Only one study yielded non-directional results with no noticeable differences between the control group and study group. CONCLUSIONS: After a thorough review of the selected research articles, it is concluded that HBOT would be an effective adjunct to SRP. Adding HBOT to a patient's treatment plan could be beneficial to many components of the periodontal ligament. IMPLICATIONS: HBOT would be a good addition to the dental field by offering a less invasive form of therapy to periodontally affected patients. Certain factors like price and duration of treatment could affect the accessibility of HBOT. Further research will help to bring HBOT into the dental field and become a widely accepted adjunct to periodontal therapy.